World development report 2005: a better investment climate for everyone (Washington, 2004)
The World Development Report (WDR) is the World Bank's annual flagship publication. Each year, the WDR seeks to expand the understanding of poverty and its causes, and sets out actions the development community can take to fight poverty in all its dimensions.
Keywords: Economic development